THE USE OF MICROWAVE HEATING FOR BAKING SEMI-FINISHED BISCUITS (Development Service Industry Management, 2023)
Most types of ready-made culinary products are subjected to various methods of heat treatment before being sold/ Thermal processes, as a rule, are very long and it is practically impossible to shorten them by traditional methods at the present time. Rolls with various fillings (chocolate, condensed milk, fruit jams), cakes and pastries have the greatest demand among biscuit products, due to the moderate quality, price and good products. In the food industry, special attention is paid to physical methods of influencing raw materials, semi-finished products and finished products, which can intensify heat exchange processes. A physical method capable of achieving these goals is heating in an electromagnetic field. Heating food products in an electromagnetic field differs from heating them due to thermal conductivity or convection. Heat arises in the heating objects themselves due to its interaction with the electromagnetic field. The use of microwave heating has significant advantages over traditional methods of thermal processing of food products. Cooking time is significantly reduced, the product is heated more evenly. Microwave devices are safe to use, easy to operate. The article considers the possibility of using microwave heating for baking a biscuit semi-finished product in order to reduce the duration of this process. The optimal amount of liquid, which must be added to the recipe to obtain a high-quality product, has been developed. The influence of the height of the dough before baking, the parameters of temperature and power of the microwave chamber on the physico-chemical (moisture, baking), structural-mechanical (density, ultimate shear stress) and organoleptic parameters of the finished biscuit was evaluated. On the basis of the conducted research, the optimal parameters for the preparation of semi-finished biscuits were obtained: the amount of water – 5% of the mass of raw materials, the initial height of the dough – 10 mm, the baking temperature –1000С, the duration of 240 s and the gradual increase in the power of the magnetron from 300 to 600 W.
Keywords: Microwave device; semi-finished biscuit; microwave heating; baking; structural and mechanical indicators; organoleptic indicators